PARTISIPASI MASYARAKAT DALAM PENYUSUNAN RENCANA PEMBANGUNAN JANGKA MENENGAH DESA (RPJMDES) DI DESA KEPER KECAMATAN KREMBUNG TAHUN 2021-2027 - Syari Nur Zahro; Lailul Mursyidah (T JDP (JURNAL DINAMIKA PEMERINTAHAN), 2025)
This research discusses the low level of community participation in the preparation of the Village Medium-Term Development Plan (RPJMDes) in Keper Village, Krembung Sub- district, Sidoarjo Regency, which can affect the effectiveness of sustainable village development. This research aims to identify the extent of community involvement in the preparation of the RPJMDes, as well as the factors that influence the level of participation. The method used in this research is descriptive qualitative, with data collection techniques through interviews, observation and documentation. The selection of informants was done by purposive sampling, including community representatives and parties involved in the RPJMDes preparation process. The results show that community participation at the planning and decision-making stages is still low, while at the implementation and utilization stages the results are more optimal. Factors affecting low participation include a lack of socialization and the involvement of women in the decision-making process. The conclusion of this study suggests that further efforts are needed to increase community participation, especially in the planning stage.